Effect of weight loss on early left atrial myopathy in obese patients without known cardiovascular disease. (13th July 2021) - Deal, O; Rayner, J; Stracquadanio, A; Wijesurendra, R; Neubauer, S; Casadei, B; Rider, O; Spartera, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BHF & NIHR BRC Introduction: Obesity is strongly associated with increased risk of heart failure and ischaemic stroke independently of associated co-morbidities. Left atrial (LA) reservoir dysfunction, a marker of atrial distensibility and compliance, is an early pathophysiological change which precedes the onset of cardiovascular disease in patients with obesity. It is unclear whether a weight loss intervention may be sufficient to reverse LA reservoir dysfunction. Purpose: To longitudinally assess whether a weight loss intervention normalizes LA reservoir function by cardiac magnetic resonance (CMR) feature-tracking in patients with obesity and only subclinical cardiovascular disease and compared this age and sex matched non-obese normal weight controls. Methods: A total of 45 patients with severe obese (age = 45 ± 11 years, body mass index = 39.1 ± 6.7 kg/m2, 51 ± 18 kg of excess body weight [EBW], 67% female) underwent CMR for quantification of LA and left ventricular (LV) size and function before and a median of 373 days following weight loss intervention. Weight loss was achieved by means of a very-low calorie diet (N = 28; 800 kcal/day) or by bariatric surgery (N = 17). A total of N = 27 non-obese healthy controls (age = 41 ± 12 years, body mass index = 22.3 ± 2.4 kg/m2, 75% female) underwent the same CMR protocol once. Results: At baseline, patients with obesity displayed signs of atrial myopathy with increased LA volume and reduced LA reservoir function as compared to normal-weight controls (both P < 0.05, Figure 1) alongside increased LV mass and hyper-normal LV ejection fraction [LVEF] (both p < 0.01). As expected, weight loss led to a significant reduction of LA volume and LV mass with normalization of LVEF regardless of the degree of weight loss achieved (all P < 0.05, Figure 2). By contrast, only a large weight loss (>46.6% EBW, in red in Figure 2) was sufficient to improve and normalize the LA reservoir function (P < 0.05, Figure 2). On the other hand, moderate or milder weight loss (in orange and red) had no significant effect on LA reservoir function (both P > 0.05). Conclusion: Successful weight loss can completely revert early LA myopathic phenotype in obese patients without known cardiovascular disease although this can be achieved only with larger weight loss targets.